Studi in Silico Lima Senyawa Aktif Sebagai Penghambat Protein Virus Dengue - Herman, Reni (Jurnal Kefarmasian Indonesia, 2019)
Dengue infection is an endemic disease in the tropics and subtropics, caused by dengue virus (DENV) infection. Some compounds have been shown to have antiviral effects on some viruses. In silico study is conducted to predict the stability of natural ingredient compounds: artemisinin, catechin, mangiferin, epigallocatechin gallate (EGCG), and quercetin in their interactions with dengue virus proteins at molecular level. This study is carried out using the 2008 version of the Molecular Operating Environment (MOE) software. Ligands are ribavirin as antiviral control whereas artemisinin, mangiferin, EGCG, and quercetin with 3D mole format structures. The downloaded DENV protein with PDB document format is the DENV serotype 2 envelope protein with 1OKE code, non structural protein 3 (NS3) with 2VBC code and NS5 protein with 1L9K code. In silico test generally showed that catechin, mangiferin, EGCG, and quercetin had more stable docking ligands to DENV’s proteins. In particular, mangiferin had stable docking ligand to envelope proteins, NS3 (helicase and protease) and in NS5-methyltransferase compared to ribavirin. Catechin stabled on NS3-protease, EGCG on NS3 (helicase and protease) and quercetin on NS3-protease. Artemisinin had less stabled bonds than ribavirin. The results indicated that catechin, mangiferin, EGCG, and quercetin had potential inhibition to DENV proteins whereas mangiferin was the most potential compound to inhibit dengue virus protein targets.